Design, fabricate and arrange a base structure for a robotic arm car - Mohd Nizam, Harris Eidman (2025)
A robotic arm car is used to pick up objects on any terrains and placing it to its designated place. There are many robotic arms created as of nowadays yet it is commonly fixed on the place it is assembled. In order to improve the designs that has been made, the objective is to design a balance and stable base structure for a robotic arm car. This project shows the detail on the process to produce the machine, from its design to fabricating it and all the manufacturing process that it will undergo. This project aims for kindergarten uses as to help caretakers in doing chores while being more relaxed and aims for exposing kids and children of the robotic world thus making them interested and excited to know more and learn more about robotics.